PENILAIAN KINERJA KEUANGAN MENGGUNAKAN ANALISIS RASIO KEUANGAN DAN ANALISIS TREND (STUDI KASUS PADA PT. XYZ PERIODE 2019-2023) - Sarah Siti Fauziah; Muhammad Nur Afif; Maria Magdalena Melani (Investama : Jurnal Ekonomi dan Bisnis, 2026)
To assess a company’s financial condition and performance, financial ratio analysis is a commonly used method. Trend analysis is a method for evaluating financial statements by observing whether a company’s performance is improving or declining over time. This study aims to analyze the financial performance of PT. XYZ from 2019 to 2023, and to examine its development trends. The analysis uses financial ratios, including liquidity, solvency, activity, and profitability ratios, along with trend analysis. The object of this research is the annual financial statements of PT. XYZ, such as the balance sheet and income statement for the 2019–2023 period. This research applies a descriptive quantitative method, and the data were collected directly from the company. The results show that, in general, the company’s financial ratios, including liquidity, solvency, activity, and profitability, are categorized as unhealthy or underperforming. However, when viewed from the trend development over the research period, the average performance has increasingly improved.